1997
DOI: 10.1073/pnas.94.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic studies with a keratin promoter-driven growth hormone transgene: Prospects for gene therapy

Abstract: Keratinocytes are potentially appealing vehicles for the delivery of secreted gene products because they can be transferred to human skin by the relatively simple procedure of grafting. Adult human keratinocytes can be efficiently propagated in culture with sufficient proliferative capacity to produce enough epidermis to cover the body surface of an average adult. However, the feasibility of delivering secreted proteins through skin grafting rests upon (i) the strength of the promoter in keratinocytes and (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 62 publications
(75 reference statements)
10
110
2
1
Order By: Relevance
“…Transgenic founders were tested for Cre activity by breeding to ROSA26R mice (B6.129S4-Gt(ROSA)26Sor tm1Sor ) (Soriano, 1999) (Jackson Laboratories). Detection of β-galactosidase in embryo wholemounts and 20 µm frozen sections of P1 tissue were as described previously (Phippard et al, 1999;Wang et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic founders were tested for Cre activity by breeding to ROSA26R mice (B6.129S4-Gt(ROSA)26Sor tm1Sor ) (Soriano, 1999) (Jackson Laboratories). Detection of β-galactosidase in embryo wholemounts and 20 µm frozen sections of P1 tissue were as described previously (Phippard et al, 1999;Wang et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the requirement for Bmpr1a in development of the epidermis and its appendages, we generated three lines of transgenic mice that constitutively express Cre recombinase in epidermal cells under the control of a well-characterized keratin 14 (K14) promoter (Wang et al, 1997). This promoter is active in surface ectoderm and basal epidermis from embryonic day (E) 9.5, and drives expression in developing hair follicle and tooth epithelia (Byrne et al, 1994;Dassule et al, 2000).…”
Section: Generation Of Mice Lacking Bmpr1a In the Epidermis And Its Dmentioning
confidence: 99%
“…2 Skin grafting procedures have been established for the clinical treatment of burned patients. 3 These achievements provide the tools to manipulate large amounts of skin cells ex vivo and prepare the ground for skin gene therapy ex vivo.…”
mentioning
confidence: 99%
“…21 High concentrations of transcription products in both the dermis and epidermis have been achieved using cytomegalovirus (CMV) promoters. 22 We found that gene gun administration of pCMV-hASP caused the local skin melanin index of rats to decrease by 70% (Figure 2).…”
Section: Seeing the Gene Therapy C-h Yang Et Almentioning
confidence: 99%